The influence of social identity on self-worth, commitment, and effort in school-based youth sport - Martin, L. J.; Balderson, D.; Hawkins, M.; Wilson, K.; Bruner, K. W. (Journal of Sports Sciences, 2018)
The current study examined the influence of social identity for individual perceptions of self-worth, commitment, and effort in school-based youth athletes. Using a prospective research design, 303 athletes (Mage = 14.89, SD = 1.77; 133 female) from 27 sport teams completed questionnaires at 2 time points (T1 - demographics, social identity; T2 - self-worth, commitment, effort) during an athletic season. Multilevel analyses indicated that at the individual level, the social identity dimension of in-group ties (IGT) predicted commitment (b = 0.12, P = .006) and perceived effort (b = 0.14, P = .008), whereas in-group affect (IGA) predicted commitment (b = 0.25, P = .001) and self-worth (b = 2.62, P = .006). At the team level, means for IGT predicted commitment (b = 0.31, P < .001) and self-worth (b = 4.76, P = .024). Overall, social identity accounted for variance at both levels, ranging from 4% (self-worth) to 15% (commitment). Identifying with a group to a greater extent was found to predict athlete perceptions of self-worth, commitment, and effort. More specifically, at the individual level, IGT predicted commitment and effort, and IGA predicted commitment and self-worth. At the team level, IGT predicted commitment and self-worth.